PERTUMBUHAN EKSPLAN PUAR TENANGAU (Elettariopsis sp.) SECARA IN VITRO - Triningsih Triningsih; Luthfi A Mahmud Siregar; Lollie A. P. Putri Agustina P Putri (Jurnal Agroekoteknologi, 2013)
Puar tenangau is a herbal plant of Zingeberaceae that from Thailand. The Plant has a big potential as pharmacy and traditional medicines, but the spread of this plant was unknown well in Indonesia even so needed a conservation for this plant. In vitro conservation is a one of alternative. In in vitro method, adding plant growth regulator is needed like Auxine and cytokinine.  Napthtalen-3-Acetid is kind of auxine that good to root growth and Benzil amino purin is kind of cytokinin to shoot growth. The research aimed to know the influence of Benzylamino purine (BAP) and Napthtalen-3-acetid acid (NAA) concentration on the growth of puar tenangau.The research was carried out in the Tissue Culture Laboratory, Agriculture’s Faculty of Nort Sumatera University from March to June 2012. This research used Completely Randomized Design with two factors. First factor was BAP concentration consist of four levels:0 mg/l; 2 mg/l; 4 mg/l; 6 mg/l. The second factor was NAA concentration consist of three levels are 0 mg/l; 1.5 mg/l; 3 mg/l. The results showed that BAP concentration give effect significantly only on leaves number in 12 weeks after planting, but it have no effect significantly on the percent of living explant, plantlet height, leaves number on 4 and 8 weeks after planting. NAA and interaction of BAP and NAA have no effect significantly to living explant, plantlet height, leaves number on 4,8 and 12 weeks after planting.   Keywords: puar tenangau, BAP,NAA, In vitro.